2018
DOI: 10.2196/jmir.9373
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Users’ Vaping Experiences from Social Media: Initial Study Using Sentiment Opinion Summarization Techniques

Abstract: BackgroundE-liquid is one of the main components in electronic nicotine delivery systems (ENDS). ENDS review comments could serve as an early warning on use patterns and even function to serve as an indicator of problems or adverse events pertaining to the use of specific e-liquids—much like types of responses tracked by the Food and Drug Administration (FDA) regarding medications.ObjectiveThis study aimed to understand users’ “vaping” experience using sentiment opinion summarization techniques, which can help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There have been few studies on flavor sentiment analysis on social media [ 16 , 26 ]. One study focused on e-cigarette–related Twitter post sentiments among users with respect to different genders and age ranges [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few studies on flavor sentiment analysis on social media [ 16 , 26 ]. One study focused on e-cigarette–related Twitter post sentiments among users with respect to different genders and age ranges [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, flavor-related sentiments were not discussed. Another study showed the sentiments on e-liquid flavors mentioned on JuiceDB, but only focusing on the 2 most popular flavors, fruit and sweet flavors [ 26 ]. Our results were similar to the sentiment analysis from JuiceDB, showing that the overall sentiments for those 2 flavors were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the association of user-reported health risks with e-cigarette flavorings could be explored from social media posts. A recent review on e-liquid flavors using the JuiceDB data from 2013 to 2017 found that Fruity and Sweet were the two most popular e-liquid flavors and have more positive sentiments from users [ 14 ]. However, possible associations of e-liquid flavors with health risks have not been well investigated using social media data.…”
Section: Introductionmentioning
confidence: 99%
“…Vaping has been studied through the lens of Internet data. Social media data was the source of several studies, including Twitter [20,21], JuiceDB (a social media platform for people who vape) [22], YouTube [23], Reddit [24], and mobile apps [25]. The health effects of vaping were examined in Reddit data by Chen et al [26] and in JuiceDB by Li et al [22].…”
Section: Introductionmentioning
confidence: 99%